Bamboo leaf: A review of traditional medicinal property, phytochemistry, pharmacology, and purification technology. (24th April 2023) - Cheng, Yaqian; Wan, Siqi; Yao, Linna; Lin, Ding; Wu, Tong; Chen, Yongjian; Zhang, Ailian; Lu, Chenfei
Abstract: Ethnopharmacological relevance: Bamboos are perennial evergreen plants that belong to the subfamily Bambusoideae of the true grass family Poaceae, with more than thousands of species distributed around the world. They are used as a traditional medicine with demonstrated effects of anti-oxidation, free radical scavenging, anti-inflammatory, liver protection and ameliorating cognitive deficits. Bamboo leaf is mainly used for the treatment of atherosclerotic, diabetic and nervous system diseases. Aim of the study: This review aims to provide up-to-date information on the traditional medicinal properties, phytochemistry, pharmacology, and purification technologies of bamboo leaf. Materials and methods: Relevant information on bamboo leaf was obtained by an online search of worldwide accepted scientific databases (Web of Science, ScienceDirect, Elsevier, SpringerLink, ACS Publications, Wiley Online Library and CNKI). Results: More than 100 chemical compounds, including flavonoids and flavonoid glycosides, volatile components, phenolic acids, polysaccharide, coenzyme Q10, phenylpropanoid and amino acids have been reported to be present. These compounds were usually extracted by column chromatography and membrane separation technologies. Preparative high performance liquid chromatography (PHPLC), high-speed counter-current chromatography (HSCCC), simulated moving bed chromatography (SMB) and dynamic axial compression chromatography (DAC) were the advanced separation technologies have been used to isolate C-glycosides from bamboo leaf flavonoid, the main bioactive ingredient of bamboo leaf. Currently, bamboo leaf is mainly used for the treatment of atherosclerotic, diabetic, hepatic diseases and nervous system related symptoms, which are attributed to the presence of bioactive components of bamboo leaf. Conclusions: Phytochemical and pharmacological analyses of bamboo leaf have been revealed in recent studies. However, most of the pharmacological studies on bamboo leaf have focused on bamboo leaf flavonoids. Further studies need to pay more attention to other phytochemical components of bamboo leaf. In addition, there is lack of sufficient clinical data and toxicity studies on bamboo leaf. Therefore, more clinical and toxicity researches on this plant and constituents are recommended. Graphical abstract: Image 1 Highlights: Bamboo leaves are traditional herbal medicines and food raw materials. The chemical ingredients and purification methods of bamboo leaf extracts are illustrated. Bamboo leaf extracts possess many excellent pharmacological properties. Existing issues and potential development prospect are discussed.